STRATEGI GROWTH HACKING DAN KEWIRAUSAHAAN INOVATIF: BAGAIMANA START-UP MENGUBAH USER ENGAGEMENT MENJADI USER RETENTION JANGKA PANJANG PADA START-UP KOTA BANDUNG - Reza Fauzi Bukhori; Eny Nuryani Resmiawati; Ooy Siti Halimah (KarismaPro, 2026)
This study aims to analyze the influence of Growth Hacking Strategies and Innovative Entrepreneurship on long-term User Retention, with User Engagement acting as a mediating variable. This research adopts a quantitative method using a causal survey approach. Data were collected through structured online questionnaires distributed to active digital start-up users (e-commerce, fintech, edutech, and ride-hailing platforms) in Bandung, West Java. Purposive sampling was applied to obtain a final sample of n = 210 respondents who met specific criteria. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) via SmartPLS 4. The findings reveal that both Growth Hacking and Innovative Entrepreneurship exert a positive and significant direct effect on User Retention. Furthermore, User Engagement significantly and partially mediates these relationships, showing the highest direct path coefficient to long-term retention. Practically, the results imply that digital start-ups should shift their KPIs from mere acquisition metrics to user-centric engagement loop models, supported by agile digital marketing strategies that foster consistent customer transaction convenience. Keywords: Growth Hacking, Innovative Entrepreneurship, User Engagement, User Retention, Bandung Start-U